Situating Vocational Learning and Teaching Using Digital Technologies - A Mapping Review of Current Research Literature - Dobricki, Martin; Evi-Colombo, Alessia; Cattaneo, Alberto (International Journal for Research in Vocational Education and Training, 2020)
Context: The ongoing change of work life by digital technologies requires vocational education and training (VET) to adapt constantly. This "digital transformation" of work life gives therefore rise to the question how to advance the use of digital technologies in VET. A possible answer may be found by considering that VET should be transferable to work life. This goal may be achieved by coupling educational activities with examples of work situations. Such situated education may be accomplished by using digital technologies. Until five years ago this mainly consisted in using digital photos, videos, and the internet for educational scaffolding or learning tasks. In research this situated digital VET taxonomy is currently expanding. Hence, the use of digital technologies in VET may be advanced by considering current research literature on situated digital VET. Method: Here, we have searched and reviewed scientific publications on situated digital VET published in the past five years. In the peer-reviewed publications that we had selected, we first identified which digital technologies were used for situated VET and which educational activities were coupled with work situation examples. Subsequently, we identified the categories to which the publications could be grouped together by analyzing the content of their full texts. Results: Situated digital VET was accomplished in about half of the reviewed publications by a digital video on a work situation, and in almost half of the publications by a work situation presented in a 3D virtual environment. Digital videos on work situations mostly served all types of learning tasks and rather rarely educational scaffolding. Work situations presented in 3D virtual environments mostly served cognitive or behavioral learning tasks and never educational scaffolding. Situated digital VET was moreover accomplished by using the digital representation of a work situation that either had occurred previously or that was immediately taking place. Conclusions: Our findings suggest that retrospectively and immediately situated digital VET may be the two categories of an up-to-date basic taxonomy of situated digital VET. Hence, an important question to investigate for advancing the use of digital technologies in VET is the following: Which of the two identified types of situated digital VET can facilitate which kind of vocational learning? Based on the reviewed publications we are not able to give any answers to this. Hence, there is a massive need to investigate which kind of vocational learning can be facilitated by retrospectively, and which by immediately situated digital VET.